On the plasma chemistry of a cold atmospheric argon plasma jet with shielding gas device. (10th December 2015) - Schmidt-Bleker, Ansgar; Winter, Jörn; Bösel, André; Reuter, Stephan; Weltmann, Klaus-Dieter
Abstract: A novel approach combining experimental and numerical methods for the study of reaction mechanisms in a cold atmospheric plasma jet is introduced. The jet is operated with a shielding gas device that produces a gas curtain of defined composition around the plasma plume. The shielding gas composition is varied from pure to pure . The density of metastable argon in the plasma plume was quantified using laser atom absorption spectroscopy. The density of long-living reactive oxygen and nitrogen species (RONS), namely, , , , and, was quantified in the downstream region of the jet in a multipass cell using Fourier-transform infrared spectroscopy (FTIR). The jet produces a turbulent flow field and features guided streamers propagating at several that follow the chaotic argon flow pattern, yielding a plasma plume with steep spatial gradients and a time dependence on the scale while the downstream chemistry unfolds within several seconds. The fast and highly localized electron impact reactions in the guided streamer head and the slower gas phase reactions of neutrals occurring in the plasma plume and experimental apparatus are therefore represented in two separate kinetic models. The first electron impact reaction kinetics model is correlated to the LAAS measurements and shows that in the guided streamer head primary reactive oxygen and nitrogen species are dominantly generated from . The second neutral species plug-flow model hence uses an source term as sole energy input and yields good agreement with the RONS measured by FTIR spectroscopy.